Magnificent 7: unsustainable growth and systemic risk - Grobys, Klaus (Aarhus University, 2025)
Faster-than-exponential growth is unsustainable, culminating in what physicists term a “finite-time singularity,” marked by abrupt regime changes. This study shifts focus from traditional systemic risks to hypothesize that the massive market capitalization of the “Magnificent 7” companies poses a systemic risk under two conditions: (a) their stocks exhibit super-exponential growth, and (b) finite-time singularities occur simultaneously. Applying the log-periodic power law (LPPLS) model to daily log-price data from May 13, 2016, to January 17, 2025, this research identifies strong evidence of bubble formations in four of the seven stocks. The LPPLS model forecasts regime changes between February and June 2025. Given the unparalleled market capitalization of these companies, their concurrent collapse could destabilize the broader financial ecosystem. We note, however, that policy interventions, particularly those effective during the Trump administration, can influence or disrupt the endogenous stock price dynamics uncovered in this analysis. In this study, such policy interventions are regarded as exogenous shocks and are not formally modeled within the LPPLS framework.
Keywords: Magnificent 7; Systemic Risk; Log-Periodic Power Law Singularity; Finite-time Singularity; Bubble; Log-periodic power laws; Singularity; Finance; Rahoitus